Formulation and Evaluation of Antioxidant Peel-Off Face Mask Containing Red Dragon Fruit Rind Extract (Hylocereus polyrhizus Haw.) - Trasna Arman Jani; Aliefman Hakim; Yohanes Juliantoni (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2020)
Peel-Off face mask is one of the cosmetics that is used to treat skin from free radicals. Peel-off face mask can minimize the effects of free radicals because it contains antioxidant. One of the antioxidant sources is red dragon fruitÃ¢â¬â¢s rind (Hylocereuspolyrhizus Haw.). The aim of this study is to obtain Peel-Off face mask of red dragon fruitÃ¢â¬â¢s rind extract that contains anthocyanin. Red dragon fruitÃ¢â¬â¢s rind was macerated by ethanol 96%, ethyl acetate and n-hexane added citric acid (4:1) solvents. TLC test used Chloroform: ethyl acetate: n-butanol (5:4:1) eluent and sprayed by AlCl3. Antioxidant activity of extract was tested using DPPH (1,1-Diphenyl-2-Picryhidrazyl) method. Peel-Off face mask was made using PVA, HPMC, methyl paraben, propylparaben, propylenglycol, extract, ethanol 96% and aquadest. The rendemen of ethanol 96% extract was 9,476%, ethyl acetate extract was 0,783% and n-hexane extract was 0,631%. The results of TLC test showed yellow spots on the ethyl acetate and ethanol 96% extracts which indicated that extract contained flavonoids (anthocyanin). The results of antioxidant activity test showed that IC50 value of ethanol 96% extract was 189,7422 (AAI=0,2087), ethyl acetate extract was 196,9398 (AAI=0,2011), and n-hexane extract was 385,3664 (AAI=0,1027). The result of the product evaluations showed that all the formulas complied the product requirements such as the organoleptic, homogenity, pH, dispersive power and drying time. Peel-off face mask already meet the product requirements but further research is needed to test the product stability and activity.